Kombinasi Agens Pengendali Hayati untuk Pengendalian Penyakit Bawang Merah di Lapangan - Wiyono, Suryo; Widodo, Widodo; Khamidi, Thamrin; Sobir, Sobir; Suryaningsih, Andika Septiana (Jurnal Fitopatologi Indonesia, 2023)
Combination of Biocontrol Agents to Control Shallot Disease in The FieldShallot production in Indonesia faces serious pest and disease problems. The use of pesticides has been using as the main practice by shallot farmers for controlling pests and diseases. Several biocontrol agents for shallot pests and pathogens have been shown to be effective individually, but have not been integrated in the field. The aim of the study was to evaluate the combination of biocontrol agents with the best effectiveness in reducing the incidence of the main shallot diseases in the field. Field trials were conducted in Tegal, Central Java, one of the shallots producing regions in Indonesia. The treatment consisted of a combination of non-pathogenic Fusarium (FNP) + plant growth promoting rhizobacteria (PGPR) + yeast antagonist (KA), FNP + KA, PGPR + KA, FNP + PGPR, synthetic fungicide, and no treatment (control). The study was arranged in a randomized block design with four block replications. All combination of biological control agents and synthetic fungicides showed significant differences with the control treatment in suppressing stem rot (Fusarium oxysporum f. sp. cepae) and purple spot (Alternaria porri) diseases, but not significantly different among them. The productivity of shallots treated with biological control agents had a relatively high fresh tuber weight. Plants treated with PGPR + KA and FNP + PGPR had the highest fresh tuber weight among other biological control agents. This study shows that the application of a combination of biological control agents has the potential to suppress shallot disease in the field.